Application of blockchain technology in copyright protection of digital music information. (15th May 2023) - Wen, Xinglin
Currently, a large amount of information is stored in digital form. There have been many information security problems, leading to the emergence of a large number of pirated digital products. Although there have been many protection measures for digital information copyright, the research content on copyright protection for digital music information is still very little. Aiming at the problems of low data storage security, long confirmation period and vulnerability to attacks in the confirmation system of digital music copyright, combined with Blockchain Technology (BT), a scheme for credible confirmation of digital music copyright is proposed. The experimental results reveal that the DPBFT algorithm can accommodate up to two faulty nodes, which has a higher fault tolerance rate than the traditional PBFT algorithm. The average throughput can reach 1249, which can meet the needs of the music copyright management system and has practical application value.